Experience of gerotranscendence among community‐dwelling older people: A cross‐sectional study. (30th December 2019) - Jeong, Sarah Yeun‐Sim; Moon, Kyoung Ja; Lee, Woo Suck; David, Michael
Abstract: Aims and objectives: To investigate the experience of gerotranscendence among older people in community in Korea and the factors that influence their experience. Background: While the literature provides estimates of how many older people are affected by negative aspects of ageing, it is not known to what extent and why some older people experience gerotranscendence, despite the challenges they encounter throughout their lifetime. Design: A cross‐sectional survey. Methods: A 55‐item questionnaire was distributed to 109 older people between March and June 2017. Univariable and multivariable linear regressions were conducted on the four question group sum scores to identify factors associated with gerotranscendence. Results: Older people aged 65–93 who live in a community in Korea reported the experience of gerotranscendence. Age and religion showed a statistically significant association with gerotranscendence. Religiosity showed a statistically significant association with beliefs about death and dying. Age and beliefs about death and dying have significant relationship with the experience of gerotranscendence. Conclusions: Older people who have more positive views about death and dying are more likely to experience gerotranscendence. The study results provide nurses and other healthcare professionals with new understandings and insights about the factors potentially related to positive ageing process. Implications for practice: It is essential for nurses to investigate their own beliefs about death and dying, and their understanding of gerotranscendence which will contribute to developing education programs and practice guidelines as an essential part of promoting gerotranscendence and positive ageing.